Pointed and Tramtrack69 establish an EGFR-dependent transcriptional switch to regulate mitosis. - Baonza, A; Murawsky, C; Travers, A; Freeman, M (2002)
Cell division in animals must be regulated; during development, for example, proliferation often occurs in spatially and temporally restricted patterns, and loss of mitotic control underlies cancer. The epidermal growth factor receptor (EGFR) has been implicated extensively in the control of cell proliferation in metazoans; in addition, hyperactivity of the EGFR and its three relatives, ErbB2-ErbB4, are implicated in many cancers. But little is known about how these receptor tyrosine kinases regulate the cell cycle. In the developing Drosophila melanogaster imaginal eye disc, there is a single patterned mitosis that sweeps across the eye disc epithelium in the third larval instar. This 'second mitotic wave' is triggered by EGFR signalling and depends on expression of String, the Drosophila homologue of Cdc25 phosphatase, the ultimate regulator of mitosis in all eukaryotic cells. Here we show that two antagonistic transcriptional regulators, Pointed, an activator, and Tramtrack69, a repressor, directly regulate the transcription of string. The activity of at least one of these regulators, Pointed, is controlled by EGFR signalling. This establishes a molecular mechanism for how intercellular signalling can control string expression, and thereby cell proliferation.